Chemical and Antimicrobial Evaluation of the Leaves ofTalinum triangulare(Jacq) Willd - Ganapaty, S.; Nyamathulla, S.; Srilakshmi, G.V.K.; Nagashyam Babu, B. (Asian Journal of Chemistry, 2010)
The methanolic extracts of Talinum triangulare on chromatography yielded five compounds, which were identified as β-sitosterol, oleanolic acid, oleanolic acid glycoside, oleanolic acid rhamno glucoside and β-sitosterol-3-β-D-glucoside. These were characterized by chemical tests and spectral means (UV, IR, MS, 1H NMR). The methanolic extract of Talinum triangulare was also screened for antimicrobial studies. A moderate activity was observed on tested organisms.